Top5itis Revisited: Some Thoughts on the Notion of General Interest in Economics - Roberto Serrano (Ensayos Revista de Economía, 2024)
Top5itis is a disease that currently affects the economics discipline. It refers to the obsession of the profession of academic economists with the so-called “top5” journals, also referred to as “top general-interest” journals. This paper offers some thoughts regarding the notion of “general-interest” in economics and discusses some of the practices in these journals.